EVALUASI SISTEM PENGENDALIAN INTERN ATAS PENJUALAN DAN PENERIMAAN KAS PADA CV. SUMATERA - Romy Wanda Taruna; Abu Kosim; Dewa Saputra (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2013)
Internal Control System is a process undertaken to provide reasonable assurance of achieving the objectives of the three classes of constraints of financial reporting, compliance with applicable laws and regulations, effectiveness, and efficiency of the operations. The purpose of this study was to determine the control procedures sales, cash receipts, and provide an evaluation of the results obtained. Object of this study is CV. SUMATERA. The methods of data collection is by interview, documentation, and observation. Problem solving is done by identifying and evaluating the internal control of the sales and cash receipts procedures, both the document and the related functions of sales and cash receipts. The results of this study indicate that the system of internal control over sales in the CV. SUMATERA has gone well and in accordance with procedures. Meanwhile, for Internal control system of cash receipts on the CV. SUMATERA have not been going well .